Reducing children's exposure to environmental tobacco smoke: the empirical evidence and directions for future research - Hovell, M. (BMJ Group, 2000)
OBJECTIVE—To summarise the issues and empirical evidence for reduction of children's residential environmental tobacco smoke (ETS) exposure. DATA SOURCES—Literature was obtained by computer search, with emphasis on studies that included quantitative measures of ETS exposure in children's residences and interventions based on social learning theory. STUDY SELECTION—Review and empirical articles concerning ETS exposure were included and inferences were drawn based on a synthesis of these studies as contrasted with a quantitative meta-analysis. DATA SYNTHESIS—Interventions designed for residential/child ETS exposure control have included policy/legal regulations, minimal clinical services, and counselling services. Divorce court and adoption services have limited custody to protect children from ETS exposure. Controlled trials of clinicians' one time counselling services have shown null results. One controlled trial found that repeated physician ETS counselling increased parent cessation. Three trials found that repeated counselling/shaping procedures reduced quantitative estimates of ETS exposure in asthmatic children. CONCLUSIONS—Insufficient controlled studies of repeated session counselling procedures have been completed to determine efficacy for ETS exposure reduction, but evidence is promising. One time minimal interventions appear ineffective, but large scale studies may be warranted. No studies have been conducted to assess court or adoption agency regulations; no community ordinances for regulating residential ETS exposure have been invoked. Ethical and enforcement issues are discussed.   Keywords: environmental tobacco smoke; passive smoking; interventions; counselling